Kontribusi Kompensasi Terhadap Kepuasan Kerja Karyawan Unit Usaha Pondok Pesantren La Tansa Cipanas Di Kabupaten Lebak - Hurriyah Agustini; Dede Kurniadi; Wildan . (E-Journal Studia Manajemen, 2013)
The purpose of this research was to examine empirically the effect between compensation on job satisfaction among the employees at La Tansa boarding school in Cipanas, Lebak regional. The subjects of this research were 43 employees selected as samples by using proportion sampling technique taken from the overall population of 43 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ job satisfaction was positively affected by the compensation in La Tansa boarding school in Cipanas, Lebak regional. The findings suggest that the variation of the job satisfaction of the employees might have been affected by compensation.